Emerging market firms in the global economy - Kumar, Vikas; Pattnaik, Chinmay (Emerald, 2014)
The adoption of pro-market economic reforms by emerging market economies in the last two decades has transformed the institutional context for firms in these economies. The objective of this volume is to better understand how domestic and foreign firms have transformed their strategy, organization and management system in response to this change. Understanding of such transformation will provide implications to integrate contextual factors in theorizing about firm behaviour in emerging as well as developed economies. These studies will also assist practicing managers to comprehend various configurations of firm activities and complexities of competition in diverse institutional settings.
Keywords: Developing countries -- Economic conditions.